القيم التنظيمية من المنظور الاسلامي - برقوق, الأستاذ الدكتور: عبد ا; قريشي, الأستاذة: نجاة، (Sciences de l'Homme et de la Société, 2015)
تعتبر القيم التنظيمية الموجه الأساسي للسلوك داخل المنظمة، فهي تمثل مجموعة الأفكار والمعتقدات السائدة في بيئة العمل والتي تكون لدى المديرين والمسؤولين في المنظمة والتي تؤثر في سلوكهم وسلوك مرؤوسيهم. وللقيم التنظيمية أهمية بالغة من المنظور الإسلامي، ولكن قل ما نجد مراجع أو دراسات تركز على هذا الجانب، لذا حاولنا من خلال هذا المقال التطرق إلى هذا الجانب وتوضيح كيف أن الإسلام أعطى للقيم التنظيمية أهمية بالغة تقوم على الأخلاق الفاضلة والقيم النبيلة.   Abstract : Organizational values Considered that the-oriented basic behavior within the organization they represent a set of ideas and beliefs in the work environment and that are among managers and officials of the organization and that affect their behavior and the behavior of their subordinates, and the values of organizational extremely important from an Islamic perspective, but Say what we find references or studies focused on this side, so we have tried through this article to address this aspect and illustrate how Islam gave great importance organizational values based on morality and noble values.